Innovation Strategy and Cost Management in Entrepreneurial Firms: Evidence from Emerging Markets - Rufayda Qiana Nusayba (Journal of Business Innovation and Accounting Research, 2025)
This study investigates the relationship between innovation strategy and cost management practices in entrepreneurial firms operating within Indonesia's emerging market context. Drawing upon resource-based theory and dynamic capability perspectives, this research examines how entrepreneurial orientation, strategic alignment, and innovation capabilities influence firm performance through effective cost management mechanisms. Utilizing a quantitative research design with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from entrepreneurial firms across various sectors in Indonesia. The findings reveal that innovation strategy significantly mediates the relationship between entrepreneurial orientation and firm performance, while cost management practices serve as critical moderating factors in this relationship. Furthermore, the study demonstrates that market orientation and adaptability to the business environment play essential roles in translating innovation strategies into sustainable competitive advantages. The results contribute to the entrepreneurship literature by providing empirical evidence from an emerging-market perspective, highlighting the unique challenges and opportunities faced by Indonesian entrepreneurial firms in balancing innovation investments with cost-efficiency imperatives. Practical implications suggest that entrepreneurial firms in emerging markets should adopt integrated approaches that align innovation strategies with systematic cost management frameworks to achieve superior performance.